A Comprehensive Analysis of Moist Versus Non‐Moist Dressings for Split‐Thickness Skin Graft Donor Sites: A Systematic Review and Meta‐Analysis - Chun‐Yee Ho; Hsuan‐Yu Chou; Szu‐Han Wang; Ching‐Yu Lan; Victor Bong‐Hang Shyu; Chih‐Hao Chen; Chia‐Hsuan Tsai (Health Science Reports)
ABSTRACT Background and Aims This systematic review and meta‐analysis evaluate the efficacy of moist versus non‐moist dressings for split‐thickness skin graft (STSG) donor sites, focusing on time to healing, pain management, and adverse events to guide clinical practice. Methods A comprehensive literature search was conducted across databases including Ovid/MEDLINE, Embase, Cochrane CENTRAL, Cochrane Database of Systematic Reviews, and Scopus up to November 28, 2023. The study adhered to PRISMA guidelines. Eligible randomized controlled trials (RCTs) were assessed for quality using the Newcastle‐Ottawa Scale and Cochrane risk‐of‐bias tool, with meta‐analysis performed using the DerSimonian and Laird random‐effects model. Results Out of 464 identified studies, 16 RCTs involving 1129 patients were included. Moist dressings such as Tegaderm, Hydrocolloid, Alginate, polyurethane, and hydrofiber showed a faster mean time to healing compared to non‐moist dressings like Mepitel and paraffin‐impregnated gauze. Hydrocolloid dressings were particularly effective in accelerating wound healing. Additionally, moist dressings were associated with lower pain levels during dressing removal and had comparable rates of adverse events. Conclusion The evidence strongly supports the use of moist dressings, particularly Hydrocolloid, for STSG donor site coverage. These dressings promote faster healing and superior pain management. The study highlights the need for further research to address existing limitations and refine recommendations for optimal wound care interventions.